2022
DOI: 10.3390/app12031710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Alkali Metals and Organic Cations to Cu-Based Perovskite Solar Cells

Abstract: First-principles electronic band calculations were used to investigate the effects of alkali metals and organic cations added to Cu-based perovskite solar cells. The copper d-orbital band was slightly above the valence-band maximum and functioned as an acceptor level for carrier generation. Excitation from iodine p-orbitals and copper d-orbitals to alkali metal s-orbitals could suppress carrier recombination and promote carrier transport. Experimental solar conversion efficiencies increased after adding both C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The perovskite crystals with supercells of 2 × 2 × 2 as cluster models were constructed, as reported in the previous works. [51][52][53][54] The molecular behavior and thermodynamic stabilities of Ge, Cu and organic cations were calculated by CPMD. After equilibration of the electronic and atomic states, MD calculations were performed at a constant temperature of 300 K. Planewave basis set cut offs for the wave functions and charge density were set at 50 and 200 Rydberg.…”
Section: Experimental and Calculation Methodsmentioning
confidence: 99%
“…The perovskite crystals with supercells of 2 × 2 × 2 as cluster models were constructed, as reported in the previous works. [51][52][53][54] The molecular behavior and thermodynamic stabilities of Ge, Cu and organic cations were calculated by CPMD. After equilibration of the electronic and atomic states, MD calculations were performed at a constant temperature of 300 K. Planewave basis set cut offs for the wave functions and charge density were set at 50 and 200 Rydberg.…”
Section: Experimental and Calculation Methodsmentioning
confidence: 99%
“…[36][37][38][39] In addition, simultaneous addition of CuBr 2 with alkali elements and organic cations provided reduction of crystal lattice distortion, suppression of defects, and improvement of device stability. [40][41][42][43] However, first-principles calculations and experiments have shown that the introduction of Cu 2+ into the B site in perovskite crystals destabilizes the crystal structure and reduces device stability. 44) For device durability, it was reported that the simultaneous addition of Cu 2+ and stable organic cations compensates the structural destabilization caused by Cu 2+ substitution.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] These improvements in the film qualities of the perovskite compounds were attributed to the introduction of Cu, which delayed the growth rate of perovskite crystals. 14) Co-addition of Cu and alkali metals to MA-based perovskite has also been reported to enhance photovoltaic properties [15][16][17][18] or device stabilities. [18][19][20] The Cu addition reduced the crystal lattice distortion, and the alkali metals migrated to the vacancy sites due to MA desorption, suppressing the lattice defects.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies by the first-principles calculations indicated that the crystal structure would be stabilized by introducing ethylammonium (EA), which have a larger ionic radius than MA. 16,23) It has been reported that the EA addition to perovskite precursor solutions promoted crystal growth. [24][25][26] The additions of guanidinium (GA), which has a larger ionic radius than EA, has improved the crystallinity and grain sizes of perovskite compounds.…”
Section: Introductionmentioning
confidence: 99%